The reformation of England's past - Phillpott, Matthew, author.
1 online resource (244 pages)
Keywords: This book is a detailed examination of the sources and protocols John Foxe used to justify the Reformation, and claim that the Church of Rome had fallen into the grip of Antichrist. The focus is on the pre-Lollard, medieval history in the first two editions of the Acts and Monuments. Comparison of the narrative that Foxe writes to the possible sources helps us to better understand what it was that Foxe was trying to do, and how he came to achieve his aims. A focus on sources also highlights the collaborative circle in which Foxe worked, recognizing the essential role of other scholars and clerics such as John Bale and Matthew Parker.